The Influence of Good Corporate Governance, Financial Distress, and Whistleblowing Systems on Fraud Prevention in Indonesian SOEs - Sevta Difa Marcella; Aspahani Aspahani; Hendra Susanto (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2025)
Fraud is one of the major issues affecting the stability and sustainability of companies, including State-Owned Enterprises (BUMN) in Indonesia. This research aims to examine the influence of Good Corporate Governance (GCG), financial distress, and the whistleblowing system on fraud prevention in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The study adopts a quantitative approach using secondary data obtained from the annual reports and financial statements of 22 SOEs that meet the purposive sampling criteria, resulting in 66 observations over three years. The data was analyzed using panel data regression with the Random Effect Model (REM) as the best fit. The study results show that the frequency of audit committee meetings (GCG) has a positive and significant effect on fraud prevention, while the size of the audit committee has a negative effect. Financial distress has a positive impact, reflecting stricter oversight, while the whistleblowing system has a negative but insignificant effect due to implementation challenges. Simultaneously, the three factors significantly influence fraud prevention in SOEs